Association of Calcium, Magnesium, Zinc, and Copper Intakes with Diabetic Retinopathy in Diabetics: National Health and Nutrition Examination Survey, 2007–2018. (4th May 2023) - Xu, Han; Dong, Xinxin; Wang, Jin; Cheng, Xiaowei; Qu, Shifang; Jia, Tingting; Liu, Jun; Li, Zhiyao; Yao, Yan
Abstract: Purpose: To evaluate the associations between calcium, magnesium, zinc, and copper intakes and the risk of diabetic retinopathy (DR) in US diabetes adults. Methods: Using data from the National Health and Nutrition Examination Survey (NHANES) 2007–2018. Multivariable logistic regression models and restricted cubic spline models were applied to examine the associations between total calcium, magnesium, zinc, and copper intakes and diabetic retinopathy. Results: A total of 3794 adults aged 40 years or older were included. Higher quartile intake of calcium, magnesium, zinc, and copper was associated with a lower occurrence of DR, the multivariate adjusted ORs (95% CI) were 0.57 (0.38–0.86), 0.48 (0.32–0.73), 0.58 (0.39–0.88), and 0.48 (0.30–0.77), respectively. U-shaped dose-response relationships were found between calcium, magnesium, zinc, copper intake, and the risk of DR. Conclusion: Higher total calcium, magnesium, zinc, and copper intake were inversely associated with the risk of DR in US diabetes adults.